Stitching Psalms Together On the Function and Use of Psalms in 4Q171 - Davage, David 1983- (2023)
4Q171 (4QpPsa) is one of the most well preserved pesharim among the Dead Sea Scrolls. It features three psalms, Psalms 37, 45, and 60, but in most analyses, Psalms 45 and 60 are left out. In this article I argue that analyses of 4Q171 should take the entire pesher into consideration. Proceeding from an overview and outline of the main parts, I provide an analysis of the contents and argue that clear overlaps are found among all three psalms, and that their nature points to a shared theme. I suggest that frag. 13, which contains Ps 60:8-9 and a commentary, would fit well either in the damaged col. 1, lines 5-10, before Psalm 37, or, perhaps better, at the end of a second sheet, while frags. 11-12 probably provided the first part of a fifth column. Ultimately, and although the material reconstruction will remain hypothetical, I show that the three psalms have been carefully selected to speak to the needs of the contemporary situation through a vision of an eschatological return to the land.
Keywords: 4Q171; Dead Sea Scrolls; Psalm 37; Psalm 45; Psalm 60; Psalms; Pesharim